2012
DOI: 10.1111/1574-6941.12010
|View full text |Cite
|
Sign up to set email alerts
|

NaturalizedEscherichia colifrom New Zealand wetland and stream environments

Abstract: This research investigates the presence of a naturalized clade of Escherichia coli in wetland and stream biofilms. Escherichia coli is used as a faecal indicator in water quality monitoring programmes worldwide, with the assumption that this bacterium is exclusively a commensal of the vertebrate gut. However, recent findings indicate growth and multiplication of E. coli in water and soils. This study seeks to clarify the relationships between environmental and commensal E. coli strains retrieved from New Zeala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…It is well known that TC bacteria are not reliable indicators of fecal contamination (Leclec et al ). Despite the historically accepted status of FC and EC bacteria as fairly reliable indicators of fecal contamination, recent research has shown that, like many members of the TC group of bacteria, indigenous, or environmentally adapted strains are found in the FC and EC bacteria groups as well (e.g., Perchec‐Merien and Lewis ). Krolik et al () found that perhaps as many as 49% of their sampled population of private wells contained E. coli that were likely not derived from either human or bovine fecal sources.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that TC bacteria are not reliable indicators of fecal contamination (Leclec et al ). Despite the historically accepted status of FC and EC bacteria as fairly reliable indicators of fecal contamination, recent research has shown that, like many members of the TC group of bacteria, indigenous, or environmentally adapted strains are found in the FC and EC bacteria groups as well (e.g., Perchec‐Merien and Lewis ). Krolik et al () found that perhaps as many as 49% of their sampled population of private wells contained E. coli that were likely not derived from either human or bovine fecal sources.…”
Section: Discussionmentioning
confidence: 99%
“…Studying the fate of E. coli in non-enteric habitats, and identifying environmental reservoirs, is crucial to evaluate the potential acquisition of virulence or antibiotic-resistance properties, leading to infections by pathogenic E. coli (such as the O157:H7 serotype) suspected to evolve in the environment 43 44 . Recent studies identified reservoirs such as beach sands 2 45 , marine sediments and wetlands 3 4 46 . Freshwater macroalgae, such as Cladophora , can harbor FIB in lakes 24 27 29 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Although high-tech methods are being available still there are gaps in understanding how bacteria can cope with chemicals, how they develop resistance strategies and transfer them between bacterial cells, species, or hosts. Some of the crucial restrictions are complexity of microbiota present in various ecosystems (Allen et al, 2013; Perchec-Merien and Lewis, 2013) and studies focused on selected issues at a given point of time (Dahmen et al, 2012; Wasyl et al, 2012). Human mobility and easy transfer of goods in globalized world further tangles up epidemiology of resistance (SVARM, 2012).…”
Section: Introductionmentioning
confidence: 99%